Perumusan Blue Ocean Strategy dengan Metode SWOT pada Batik Atina Solo - Gandung Kuncahyo; Yunita Primansanti; Anita Oktaviana Trisna Devi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to formulate a Blue Ocean Strategy to enhance business competitiveness through a SWOT analysis approach. The research was conducted using a descriptive qualitative method. Primary data were obtained through interviews with competent parties to identify the internal and external factors of the business, while questionnaires were used as supporting data to capture respondents’ perceptions of the identified factors. The interview results served as the basis for developing the IFAS and EFAS matrices to determine the business position within the SWOT matrix. Furthermore, the SWOT analysis results were used to formulate alternative strategies aimed at creating new value in line with the Blue Ocean Strategy concept. The questionnaire results indicate that respondents’ perceptions tend to support the internal and external factors identified through interviews, thereby strengthening the analytical findings. Based on the results, it can be concluded that formulating a Blue Ocean Strategy through SWOT analysis provides a more innovative and competitive strategic direction. The resulting strategies are expected to help businesses create sustainable competitive advantages and avoid direct competition in saturated markets.